Алгоритм прогнозування курсу криптовалюти з урахуванням впливу дописів групи відомих людей в соціальних мережах - Bidyuk, Petro; Gavrilenko, Olena; Myagkyi, Mykhailo (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2023)
This article presents an algorithm for predicting the rate of a selected cryptocurrency, taking into account the posts of a group of famous people in a particular social network. The celebrities chosen as experts, i.e., famous personalities whose posts on social networks were studied, are either familiar with the financial industry, particularly the cryptocurrency market, or some cryptocurrency. The dataset used was the actual rates of the cryptocurrency in question for the selected period and the statistics of expert posts in the selected social network. The study used methods such as the full probability formula and the Bayesian formula. It was found that posts by famous people on social media differently affected cryptocurrency rates. The “main” expert was identified, and his posts were used to forecast the selected cryptocurrency’s rate.